2021
DOI: 10.1590/1807-3107bor-2021.vol35.0096
|View full text |Cite
|
Sign up to set email alerts
|

Rethinking the decision-making process to treat gingival recession associated with non-carious cervical lesions

Abstract: The presence of a tooth-surface defect, such as a non-carious cervical lesion (NCCL), associated with sites of gingival recession (GR) defects creates a combined soft tissue/tooth defect (CD) that requires a different treatment plan. This study aimed to critically review the literature regarding the available treatment protocols for CDs and suggest a new decision-making process. NCCLs were classified as Class A-: the cementoenamel junction (CEJ) was visible and the root surface discrepancy was < 0.5 mm (no ste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
24
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(36 citation statements)
references
References 38 publications
0
24
0
3
Order By: Relevance
“…[23][24][25] The matrix was trimmed according to each defect size, placed to cover 1 to 2 mm of the restoration, and sutured independently of the flap. Thereafter, the flaps of both groups were advanced and sutured with sling and interrupted sutures 5 to cover the matrix and at least 2 mm of the apical margin of the restoration (Figures 1G and 2H).…”
Section: Surgical and Postoperative Protocolmentioning
confidence: 99%
See 3 more Smart Citations
“…[23][24][25] The matrix was trimmed according to each defect size, placed to cover 1 to 2 mm of the restoration, and sutured independently of the flap. Thereafter, the flaps of both groups were advanced and sutured with sling and interrupted sutures 5 to cover the matrix and at least 2 mm of the apical margin of the restoration (Figures 1G and 2H).…”
Section: Surgical and Postoperative Protocolmentioning
confidence: 99%
“…2 It was suggested that CD with B-and B+ NCCLs should be treated with a combination of a restorative procedure to reconstruct the coronal zone of the NCCL, up to 1 mm of the root surface, and a surgical procedure for root coverage afterward. [3][4][5] Coronally advanced flap (CAF) with connective tissue graft (CTG) has been successfully used to treat CDs. [6][7][8][9][10] A recent study showed that both CAF and CAF + CTG can be successfully used as surgical techniques to treat single partially restored CD, and CAF + CTG achieved better coverage in CDs with a thin periodontal phenotype.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In order to address the esthetic issues, periodontal root coverage surgery should be considered [ 4 ]. Combining restorative treatment with periodontal root coverage surgery is applicable to CDs, resolving both defects [ 5 , 6 ]. The detailed procedures of the combined restorative-surgery approach have been documented in previous clinical studies [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%